2020
DOI: 10.1186/s13014-020-01517-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases treated with hypofractionated stereotactic radiotherapy: 8 years experience after Cyberknife installation

Abstract: Background: Hypofractionated stereotactic radiotherapy (HFSRT) is indicated for large brain metastases (BM) or proximity to critical organs (brainstem, chiasm, optic nerves, hippocampus). The primary aim of this study was to assess factors influencing BM local control after HFSRT. Then the effect of surgery plus HFSRT was compared with exclusive HFSRT on oncologic outcomes, including overall survival. Materials and methods: Retrospective study conducted in Léon Bérard Cancer Center, included patients over 18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…Despite a lower median BED12 of 41.0 Gy being used for SRS, the rate of necrosis was significantly higher (14.8%, p = 0.045 on multivariate analysis). Rates of necrosis following HRFT are typically <10% [ 11 , 19 , 28 , 29 , 30 ], whilst SRS has been associated with necrosis in over 20% of patients in two studies, each over 250 metastases, by Minniti et al [ 11 , 31 ]. Furthermore, a meta-analysis of 24 studies comparing SRS vs. HFRT on BMs 2–3 cm in diameter demonstrated significantly less radionecrosis in the HFRT group (23.1% vs. 7.3%, p = 0.003), with no difference in LC (77.6% vs. 92.9%, p = 0.18), further suggesting that a hypofractionated approach confers a lower risk of radiation toxicity without compromising efficacy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lower median BED12 of 41.0 Gy being used for SRS, the rate of necrosis was significantly higher (14.8%, p = 0.045 on multivariate analysis). Rates of necrosis following HRFT are typically <10% [ 11 , 19 , 28 , 29 , 30 ], whilst SRS has been associated with necrosis in over 20% of patients in two studies, each over 250 metastases, by Minniti et al [ 11 , 31 ]. Furthermore, a meta-analysis of 24 studies comparing SRS vs. HFRT on BMs 2–3 cm in diameter demonstrated significantly less radionecrosis in the HFRT group (23.1% vs. 7.3%, p = 0.003), with no difference in LC (77.6% vs. 92.9%, p = 0.18), further suggesting that a hypofractionated approach confers a lower risk of radiation toxicity without compromising efficacy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This concept simplifies the management, may spare medical resources, and provide additional time for, e.g., a systemic therapy or just improve the quality of life. Backing the above-mentioned tendency to better response of smaller tumors, Lesueur et al ( 2018 ) estimated a significantly decreased risk of local control failure (from 36 to 17% at 12 months, p = 0.007) for the CK-hSRS therapy of radio-resistant BM (melanoma and renal carcinoma) showing < 1 cm in diameter and Mengue et al ( 2020 ) showed the target size of < 2.5 cm to be an independent factor improving LC in CK-hSRS therapy of BM ( p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1993, clinical application of fractionated stereotactic radiotherapy for brain metastases performed by LINAC was extensively described in the literature (Salles et al 1993 ; Manning et al 2000 ; Feuvret et al 2014 ; Lehrer et al 2019 ; Rajakesari et al 2014 ; Rades et al 2017 ; Baliga et al 2017 ; Aoyama et al 2003 ; Ernst-Stecken et al 2006 ; Aoki et al 2006 ; Narayana et al 2007 ; Kwon et al 2009 ; Saitoh et al 2010 ; Kim et al 2011 ; Minniti et al 2014 ). However, there are only few heterogeneous reports about the CK-hSRS for BM elucidating its application in different patient populations and with different study specifics (Table 5 ) (Inoue et al 2014 ; Murai et al 2014 ; Royer et al 2017 ; Nakamura et al 2017 ; Lesueur et al 2018 ; Guan et al 2020 ; Mengue et al 2020 ). It is difficult to compare the results due to different study designs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that these factors have prognostic significance. 7 , 11 , 21 , 22 SRS is an attractive palliative treatment option for multiple brain metastases due to the avoidance of alopecia and the fatigue of elective brain irradiation. Nowadays, very efficient LINAC-based solutions are available in which SRS for multiple BM can be delivered within half an hour with a high treatment plan quality.…”
Section: Discussionmentioning
confidence: 99%